دور الإدارة الإلكترونية في ترشيد الخدمة العمومية في الإدارة المحلية بالجزائر: دراسة حالة بلدية البليدة - فيسة، نورة سليمان (المركز الجامعي سي الحواس بريكة, 2021)
تهدف هذه الدراسة إلى معرفة دور الإدارة الإلكترونية في ترشيد الخدمة العمومية باعتبارها أهم الاستراتيجيات التي تقرب المواطن من الإدارة، وكذا معرفة ما سيفرزه مشروع التحول الإداري الإلكتروني على مستوى مفهوم الخدمة العمومية باعتباره نموذج يوفر الكثير من فرص الوضوح والدقة في تقديم الخدمات العامة وإنجاز المعاملات. ولمعرفة مدى نجاح الإدارة العمومية الجزائرية في ترشيد خدماتها من خلال اعتمادها للإدارة الإلكترونية، اتضح أنه رغم تطبيق الإدارة الإلكترونية بالبلدية يعد نقلة نوعية في تحسين مستوى خدماتها المقدمة للمواطنين إلا أنه يوجد بعض النقائص التي من شأنها أن تعيق الهدف الأساسي المرجو الوصول إليه من خلال هذا التطبيق، والمتمثلة في عدم وجود احتياطات أمنية وقانونية صارمة متبعة من قبلها لردع مخترقي الأنظمة وحماية تعاملاتها منهم. This study aims to learn about the role of e-administration in rationalizing the public service as it is one of the main strategies that approaches the citizen from the administration. It also aims to know what the e-administration transformation project will produce at the level of the public service concept as a model that provides much clarity and accuracy in the delivery of public services and transactions. And to find out how successful the Algerian public administration in the rationalization of its services through the adoption of e-administration, it has become clear that, although e-administration has been introduced in the municipality, which is a qualitative shift in improving the quality of its services to citizens, there are some shortcomings that could hamper the basic objective to be reached through this application. These shortcomings include the absence of strict security and legal precautions followed by it to deter the hackers and protect the dealings from them.
Keywords: الإدارة الرقمية -- الخدمات العامة -- التنمية المحلية -- المجالس البلدية -- الجزائر